The Relationship between Hosts and Guests in “Jogjarockarta” Music Festival - Peni Zulandari Suroto; Dimaz Naufal (Politeknik Negeri Bali, 2019)
Music festivals are a medium for people from all walks of life to meet and engage especially between fans and their favorite musicians. Jogjarockarta is an international rock music festival held in Indonesia in the cultural city of Jogjakarta. In 2017, a progressive music group from the US, Dream Theater, was invited to the festival and performed together with Indonesian metal and rock bands. The purpose of this study is to describe the cultural meaning of the social situation created by the 2017 Jogjarockarta music festival. The data were collected through interviews with the promoters, field observations by attending the festival, combined with secondary data from social media in the form of information and comments about the festival downloaded from different sources. It is analyzed from the perspectives of tourism and performing arts in the event. The study showed that the festival created a social situation in the form of relationship between three actors namely the Promoters, Audiences and featured Performers. It was found that there are “other“ audiences represented by the local community of the city where the festival was held to support the festival’s success. Unique roles immerged in the form of host, intermediary and guest. In the context of tourism, this study found that the hosts were the ones who went on an adventure. They had a common similarity as “givers”. The guests, as the performers, entertained their fans to peregrinate with them, while the hosts educated the guests on the local culture and wisdom which the guests could bring back home as a source of inspiration for their creative works. This study provides another perspective for the promoter or the event organizer to create “a spiritual relationship” which is “a space” to inspire other people. This understanding will, in turn, ensure the continuity for music festivals.